2021
DOI: 10.6007/ijarbss/v11-i12/11380
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of the Online Learning for Hotel Recreation: The Students Voice on the Perspectives and Challenges

Abstract: This study was conducted to identify the implementation of online learning for Hotel Recreation subject among Sungai Petani Community College students. A qualitative study involving 15 students was conducted to determine the students' views on the implementation of online learning for The Recreation Hotel subjects. The open-ended question was conducted together with all participants to collect information on the main content lime which consists of: i) the views of the students; ii) the implementation of learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…In the study by Hassan et al (2020), a weak internet connection was found to affect students' motivation in using elearning. Similarly, a study conducted by Quah and Suid (2021) at Sungai Petani Community College (KKSP) yielded similar findings. Unstable internet and insufficient data are among the challenges faced by KKSP students.…”
Section: " Increase Visits To Interesting Places" -R6 " Make Visits T...supporting
confidence: 53%
“…In the study by Hassan et al (2020), a weak internet connection was found to affect students' motivation in using elearning. Similarly, a study conducted by Quah and Suid (2021) at Sungai Petani Community College (KKSP) yielded similar findings. Unstable internet and insufficient data are among the challenges faced by KKSP students.…”
Section: " Increase Visits To Interesting Places" -R6 " Make Visits T...supporting
confidence: 53%